Integrative Informatics Analysis of Transcriptome and Identification of Interacted Genes in the Glomeruli and Tubules in CKD - Liu, Lingyun; Ma, Fuzhe; Hao, Yuanyuan; Yi, Zhengzi; Yu, Xiaoxia; Xu, Bo; Wei, Chengguo; Hu, Jinghai (Frontiers in Medicine, 2021)
Chronic kidney disease (CKD) is a complex disease in which the renal function is compromised chronically. Many studies have indicated the crosstalk between the tubule and the glomerulus in CKD progression. However, our understanding of the interaction of tubular and glomerular injury remains incomplete. In this study, we applied a meta-analysis approach on the transcriptome of the tubules and glomeruli of CKD patients to identify differentially expressed genes (DEGs) signature. Functional analysis of pathways and Gene Ontology found that tubular DEGs were mainly involved in cell assembly and remodeling, glomerular DEGs in cell proliferation and apoptosis, and overlapping DEGs mainly in immune response. Correlation analysis was performed to identify the associated DEGs in the tubules and glomeruli. Secreted protein comparison and verification experiments indicated that WFDC2 from the tubule could downregulate PEX19 mRNA and protein levels at the glomeruli in diabetic kidney disease (DKD). This study revealed the distinctive pathways of the tubules and glomeruli and identified interacted genes during CKD progression.